Breaking Out of Inequality Traps : Political Economy Considerations - Fritz, Verena; Katayama, Roy; Simler, Kenneth (World Bank, Washington, DC, 2012)
This note is based on presentations and comments by Francois Bourguignon, Frances Stewart, Leonard Wantchekon, and Nancy Birdsall (chair) at the 2008 PREM Conference session on political economy of inequality: implications for inclusive growth and focuses on actions that the World Bank may pursue to promote more inclusive growth.